Online data to contextualize waterpipe tobacco smoking establishments surrounding large US universities. (December 2019) - Colditz, Jason B; Chu, Kar-Hai; Switzer, Galen E; Pelechrinis, Konstantinos; Primack, Brian A
Waterpipe tobacco smoking has grown in popularity among US college students and is associated with serious health risks. Much of the waterpipe tobacco smoking takes place in establishments such as "hookah bars" or in lounge settings. Web-based data platforms such as Yelp have demonstrated utility in locating these establishments but are prone to over- and underestimation. The purpose of this study was to optimize strategies for algorithmically estimating the prevalence of waterpipe tobacco smoking establishments. We conducted searches for potential waterpipe tobacco smoking establishments near highly residential US universities ( N  = 41). Of 521 potential establishments, independent coders confirmed 257 as permitting waterpipe tobacco smoking. We compared four strategies for using Yelp metadata to estimate the number of confirmed waterpipe tobacco smoking establishments by location. An accuracy-weighted approach generated estimates that closely matched confirmed data without significant over- or underestimation. The use of algorithms such as these may dramatically improve the feasibility and efficacy of future research linking environmental data and health outcomes.